Building a design-driven corporate culture - Brunner, Robert, 1958- (FTPress Delivers elements., 2010)
This is the eBook version of the printed book. If the print book includes a CD-ROM, this content is not included within the eBook version. Discover the six core elements of the sustainably design-driven company: the elements of world-class "experience chain management."Six core aspects of a design driven company form the acronym FLAVOR: your mnemonic for easily recalling what to focus on as you strive towards experience chain management. The letters stand for: Flexible, Long-term vision, Authentic, Vigilant, Original, and Repeatable. Now, let's zoom in and explore what these mean and how they must synchronize ... If you liked this Element, read more from Robert Brunner and Stewart Emery, including Do You Matter?: How Great Design Will Make People Love Your Company (ISBN: 9780137142446). Available in print and digital formats.